On Some Properties of Baire-1 Functions - Fenecios, Jonald P (Archīum Ateneo, 2013)
In this paper, we give alternative proofs of some of the properties of Baire-1 functions with respect to the new characterization of Baire-1 functions due to P.Y. Lee, W.K. Tang and D. Zhao. Some well-known functions were given to illustrate some of these properties.